Networks in the Implementation of Illegal Gold Mining Countermeasure Policy in Kuantan Singingi Regency - Trio Saputra; Arief Darmawan; Rachmawati Novaria (Jurnal Borneo Administrator, 2021)
This study aims to determine the implementation of the Illegal Gold Mining (IGM) Countermeasure policy in the Kuantan Singingi Regency. This study uses a multi-sectoral multi-organizational network model consisting of a Contextual Assessment approach to understanding the environmental context and identifying stakeholders in policy implementation and joint visioning. This study critically examines the IGM in the regency in qualitative perspective from various related articles. A systematic literature review was used to analyze national and international journal articles from nine managed databases based on these concerns. From the literature review, 22 relevant research-based articles in the last 15 years from 2007 to 2020 were selected from Google Scholar, Taylor, Francis Outline, Springer Link, Emerald Insight, Science Direct, Sage Journal Online, and Oxford Cambridge. Three stages were carried out: preparation, screening and validation, and content review. The findings include 1) research showing that stakeholders involved from both government and community groups do not play an active and synergistic role in controlling IGM. 2) the implementation model of the IGM countermeasure, the government, the private sector, and the community must support each other in controlling and supervising IGM.